Influence of carbonation on the microstructure and the gas diffusivity of hardened cement pastes. (30th August 2020) - Boumaaza, Mouna; Turcry, Philippe; Huet, Bruno; Aït-Mokhtar, Abdelkarim
Highlights: De, O2 is less dependent on the relative humidity of preconditioning after carbonation. De, O2 correlates well to the mean pore diameter of the hardened cement pastes. The carbonation resistance of blended pastes with De, O2 lower than 10 -9 m ² /s is comparable to OPC pastes. Abstract: The influence of carbonation on the oxygen-effective diffusion coefficient (De, O2 ) of hardened cement pastes (HCP) is investigated in the scope of durability. Experiments are carried out on HCP made with different binders (Portland cement, fly ash, slag, metakaolin binders) and water-to-binder ratios at three relative humidity levels. At a given RH, the change in De, O2 due to carbonation depends on the mix composition. However, in most of cases, De, O2 increases after carbonation, despite the porosity clogging. This is explained by both the decrease in the water saturation degree, especially at high RH, and the change in the pore size distribution. A good correlation is found between the mean pore diameter and gas diffusivity before and after carbonation at low water saturation degree (R 2  > 0.84 on a log–log scale). De, O2 is significantly less dependent on the water saturation degree after carbonation.